Acute hypoxemia caused by Impella in a patient with fulminant myocarditis and patent foramen ovale. Issue 1 (January 2023) - Shibao, Kodai; Murasato, Yoshinobu; Araki, Masahiro; Tayama, Eiki; Fukumoto, Yoshihiro
Abstract: Impella ™ (Abiomed, Danvers, MA, USA) is effective in the acute management of fulminant myocarditis and myocardial infarction with cardiogenic shock. Here, we report a case of a 70-year-old man with fulminant myocarditis in cardiogenic shock who developed right-left shunt via patent foramen ovale during acute management with Impella 5.0, resulting in sudden hypoxemia. With combined support of veno-arterial extracorporeal membrane oxygenation and Impella (ECPELLA), his circulation and oxygenation became stable. The same phenomenon is well known in left ventricular assist device. In such situations, ECPELLA is effective to improve the hypoxic condition. It should be kept in mind that hypoxemia can occur in patients with intracardiac shunt disease when using Impella. Learning objective: Impella is effective to maintain circulation in patients with cardiogenic shock; however, several complications have been reported. Intra-cardiac shunt can suddenly cause severe hypoxemia by Impella. We should mention the presence of intra-cardiac shunt, if the patients have sudden hypoxemia when using left ventricular assist.